The role of the Shari‛ah in contemporary moral and social development - Kadouf, Hunud Abia (INSI Publications, 2012)
The modern world has increasingly witnessed paucity of people with impeccable moral standards. All forms of moral bankruptcy are being witnessed across nations of the world. Muslim nations are also not excluded from this. This ranges from homosexuality, same sex marriage, abortion, suicide, euthanasia, and corruption to mention but a few. This ultimately calls to question the impact, which the law has in the moral and social development of nations. The problem seems to be aggravated as a result of the gap and disconnection between law and morality. The tremendous impact of this on moral and social development of the society is better imagined than real. Based on this premise, the paper analyses the role of the Shari‛ah in contemporary moral and social development. In doing this, it analyses how the Shari‛ah puts in place mechanisms to ensure moral and social developments in the society. It further discusses the perspectives of the Shari‛ah to the contemporary moral issues. For this purpose, the verses of the Qur’an, Sunnah of the Prophet (s.a.w.) and opinions of learned Muslim scholars are used.